VD_FINDINFO Décision / 2024 / 233 vom 19. März 2024 - VD Tribunal cantonal (2024)
LIBÉRATION CONDITIONNELLE, REJET DE LA DEMANDE, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1bis CPP (CH), 227 al. 5 CPP (CH), 227 al. 7 CPP (CH), 228 CPP (CH)